Moderate Intensity Physical Exercise Decreases Gastrocnemius Caspase-3 Expression on Mus musculus with Statin Treatment - Junita Jeanne Paliman; Ratna Darjanti Haryadi; Rwahita Satyawati Darmanta; Willy Sandhika; Martha Kurnia Kusumawardani (Indonesian Journal of Physical Medicine & Rehabilitation, 2021)
ABSTRACTIntroduction: Dyslipidemia is a lipid metabolism abnormality marked by increase or decrease of lipid fraction in the plasma. Statin or 3-Hydroxy-3-Methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor is an important dyslipidemia medication that may induce apoptosis of the skeletal muscle.Decrease of Bcl-2 and Bax ratio causing caspase-9 activation followed by caspase-3 activation occur in apoptosis. Moderate intensity physical exercise (MIPE) decreases DNA fragmentation, increases Bcl-2 protein level and decreases Bax transcript level.Methods: Thirty healthy BALB/C strain Mus musculus divided into 3 groups: first intervention group with statin only treatment (S), second intervention group with statin treatment plus MIPE using motorized treadmill (ST), and control (C) group with no statin and nor exercise. The duration of treatmentwas 28 days. Statin treatment dose was 2.06mg/kg bodyweight. Measurement caspase-3 was done by immunohistochemistry evaluation and the expression of capase-3 was calculated by cells count which expressing caspase-3.Results: There were more muscle cells expressing caspase-3 in the S group (47.00±12.92cells) than the C group (2.70±1.94 cells); p=0.000, the ST group (21.44±10.13 cells) than the C group (p=0.001), as well as S group and the ST group (p=0.000).Conclusion: Moderate intensity physical exercise can decrease caspase-3 expression in statin treated subject.Keywords: apoptosis, caspase-3, dyslipidemia, moderate intensity physical exercise, statin.